Waol A, trans-dihydrowaol A, and cis-dihydrowaol A: polyketide-derived γ-lactones from a Volutella species - El-Elimat, Tamam (2013)
An organic extract of a filamentous fungus (MSX 58801), identified as a Volutella sp. (Hypocreales, Ascomycota), displayed moderate cytotoxic activity against NCI-H460 human large cell lung carcinoma. Bioactivity-directed fractionation led to the isolation of three γ-lactones having the furo[3,4-b]pyran-5-one bicyclic ring system [waol A (1), trans-dihydrowaol A (2), and cis-dihydrowaol A (3)]. The structures were elucidated using a set of spectroscopic and spectrometric techniques; the absolute configuration of 2 was established via a modified Mosher’s ester method. Compounds 1 and 2 were evaluated for cytotoxicity against a human cancer cell panel.